Dominant valued reasons of future rehabilitology experts while studying of discipline «massotherapy» - Єфіменко Павло Богуславович (Pavlo Iefimenko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: exposure of dominant reasons during studying of discipline «massotherapy» by the students of direction of specialize «Health of man» of Kharkov state academy of physical culture. Material and Methods: motivation of students of future rehabilitologists at the study of discipline «massotherapy» was determined by a questionnaire at the beginning and at the end of practical pursuit conducted within the framework of business game. Out of the academic group of specialization the «Physical rehabilitation» two sub-groups of students were formed. Results: the limited level of their personal interest is exposed to study the discipline of «massotherapy» and necessity to increase interest acquire its knowledge. Conclusions: positive influence of the offered method is revealed on the level of interests, values and reasons in relation to the study of discipline «massotherapy».